Estimating the likelihood of success with the initial empiric antimicrobial therapy in patients with nosocomial infections. (4th July 2017) - Bantar, Carlos; Alcázar, Gabriela; Franco, Diego; Ríos, Pablo; Mobilia, Liliana; Izaguirre, Mariano; Boleas, Mariana; Almará, Adriana; Oliva, María E
Abstract : In order to estimate the likelihood of success (SL) with the initial empiric antimicrobial therapy, the following formula was constructed with data subjected to prior clinical validation in real time: SL (%) = (Nº isolates susceptible to IEAT/Nº patients with MDI) × 100. Where the numerator of the formula represents the total number of isolates recovered from the assessed type of infection, that was susceptible to any component of empiric antimicrobial therapy (IEAT) used, and the denominator represents the total number of patients with the same assessed, but microbiologically documented infection (MDI). For male hospital-acquired urinary tract infection, only imipenem reached a suitable SL value (i.e. ≥80%). In patients with hospital-acquired peritonitis, imipenem and tigecycline–ceftazidime showed the highest coverage rates. For ventilator-associated pneumonia only imipenem yielded acceptable coverage as a single drug. Implementing the present formula instead of the regular global antibiograms used to guide the selection of the initial treatment may benefit the patient outcome and improve antimicrobial usage.